The Effect of Problem Based learning Model on Childhood Problem Solving Skills - Vita Arum Siwi; Nurul Kusuma Dewi (Institut Agama Islam Negeri Madura, 2025)
Problem-solving ability is an important skill in early childhood development. If the ability to solve problems is not fulfilled, children will find it difficult to live their daily lives and tend to blame others. The problem-based learning model uses problems as the basis for starting learning activities. This study aims to determine whether there is an effect of problem-based learning models on the problem-solving ability of children aged 5-6 years. The research was conducted at Gondangrejo Karanganyar. The approach used in this research is quantitative with the type of research Quasi experiment, using One group pretest-posttest design, which is research carried out by giving a pretest first before treatment and giving a posttest after treatment. The research subjects consisted of 27 children aged 5-6 years. Instrument validity test using expert judgment. Data were collected using test and observation techniques. Data analysis was carried out by normality test and hypothesis test using Kolmogorov-Smirnov test and Wilcoxon Test found in SPSS Version 23 for Windows application with normality test significance level >0.05 and hypothesis test significance level <0.05. The results of the hypothesis test in this study showed a value of 0.000, so it can be concluded that the problem-based learning model has an effect on the problem solving ability of children aged 5-6 years. The problem-based learning model has a positive influence on the problem-solving ability of children aged 5-6 years